Effects of surface patterning and topography on the cellular functions of tissue engineered scaffolds with special reference to 3D bioprinting. (16th January 2023) - Adhikari, Jaideep; Roy, Avinava; Chanda, Amit; D. A., Gouripriya; Thomas, Sabu; Ghosh, Manojit; Kim, Jinku; Saha, Prosenjit
Abstract : The extracellular matrix architecture of tissue organs inspires scaffold designing that utilizes hierarchical structures, geometrical patterns, and tunable topographies to mimic the biophysical and biochemical functions of the host environment. Abstract : The extracellular matrix (ECM) of the tissue organ exhibits a topography from the nano to micrometer range, and the design of scaffolds has been inspired by the host environment. Modern bioprinting aims to replicate the host tissue environment to mimic the native physiological functions. A detailed discussion on the topographical features controlling cell attachment, proliferation, migration, differentiation, and the effect of geometrical design on the wettability and mechanical properties of the scaffold are presented in this review. Moreover, geometrical pattern-mediated stiffness and pore arrangement variations for guiding cell functions have also been discussed. This review also covers the application of designed patterns, gradients, or topographic modulation on 3D bioprinted structures in fabricating the anisotropic features. Finally, this review accounts for the tissue-specific requirements that can be adopted for topography-motivated enhancement of cellular functions during the fabrication process with a special thrust on bioprinting.